HUBUNGAN TINGKAT PENGETAHUAN TERHADAP PERSONAL HYGIENE SAAT MENSTRUASI PADA REMAJA PUTRI DI SMA MUHAMMADIYAH PEKANBARU - Siti Qomariah; Sofia Afrita Sari; Sara Herlina; Wiwi Sartika; Andalia Roza (JOMIS (Journal of Midwifery Science), 2025)
Introduction Adolescence is a transition period marked by changes that vary from physical, emotional and psychological. Puberty can be seen from the emergence of secondary sexual characteristics where adolescents experience physical, emotional and social changes. In men it is marked by wet dreams, while in women it is marked by the start of menstruation. reproductive health problems in adolescent girls such as menstrual disorders, lack of knowledge and incorrect personal hygiene during menstruation, which can cause reproductive health problems such as; vaginal discharge, urinary tract infections (UTI), pelvic inflammatory disease (PID), the possibility of cervical cancer and even infertility. The highest incidence of reproductive tract infections (RTI) in the world is in adolescents (35% - 42%) and young adults (27% - 33%). The prevalence of poor personal hygiene behavior during menstruation is 83%. Objective: To determine the relationship between the level of knowledge and personal hygiene behavior among young women during menstruation at SMP Negri 6 Pekanbaru. This research method is a type of quantitative research with a correlation analytical research design. This research uses a cross-sectional method. The population of the study were all teenage girls from SMA Muhammadiyah Pekanbaru. . The sample collection technique in this research used a probability sampling technique with a simple random sampling method. Probability sampling technique is random sampling. The results show that there is no relationship between the level of personal hygiene knowledge and personal hygiene behavior at SMA Muhammadiyah Pekanbaru, with significant results or ÃƒÂÃ‚Â-value 0.552 where (p>0.05) so it can be concluded that there is no significant relationship between the level of personal hygiene knowledge and the personal hygiene behavior of teenagers during menstruation.